2010
DOI: 10.1007/s00024-010-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Searching for an Earthquake Precursor—A Case Study of Precursory Swarm as a Real Seismic Pattern Before Major Shocks

Abstract: A long-range correlation between earthquakes is indicated by some phenomena precursory to strong earthquakes. Most of the major earthquakes show prior seismic activity that in hindsight seems anomalous. The features include changes in regional activity rate and changes in the pattern of small earthquakes, including alignments on unmapped linear features near the (future) main shock. It has long been suggested that large earthquakes are preceded by observable variations in regional seismicity. Studies on seismi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The simplest way to understand such indication is the seismicity patterns and it is possible to establish relation with forthcoming earthquake by using such observations. Medium to large earthquakes are known to precede epochs of abnormal seismicity patterns as background/normal seismicity, swarm/ anomalous seismicity, quiescence and foreshocks [5,7,8,11,12].…”
Section: Resultsmentioning
confidence: 99%
“…The simplest way to understand such indication is the seismicity patterns and it is possible to establish relation with forthcoming earthquake by using such observations. Medium to large earthquakes are known to precede epochs of abnormal seismicity patterns as background/normal seismicity, swarm/ anomalous seismicity, quiescence and foreshocks [5,7,8,11,12].…”
Section: Resultsmentioning
confidence: 99%
“…Several authors (Evison, 1977;Mogi, 1977;Kanamori, 1981;Singh and Singh, 1984;Ohtake et al, 1977;Gupta and Singh, 1989;Shanker et al, 1995Shanker et al, , 2010Singh et al, 2005;Paudyal et al, 2009) have have suggested that seismicity preceding major earthquakes could be defined by the following episodes: (1) background/normal seismicity, (2) precursory swarm, (3) quiescence, (4) foreshocks and (5) mainshock. In most of the anomalous sequences, the magnitude of mainshocks observed to be 1-2 units higher than the magnitude of the largest swarm event (Evison, 1977;Singh et al, 1982Singh et al, , 2005Shanker et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…This is an indication that a possibly wider area will be placed at risk and revised estimates for magnitude and time of occurrence of the mainshock may be necessary. Several authors (Bufe et al, 1974;Sekiya, 1976;Gupta and Singh, 1989;Zheng et al, 1995;Shanker et al, 2010;Singh et al, 2010) have reported changes in seismicity patterns before the occurrence of medium to large earthquakes. Gupta and Singh (1986) observed that it is important to recognise swarm and quiescence before the occurrence of the mainshock and made successful prediction of 06 August, 1988 Indo-Burma border earthquake.…”
Section: Introductionmentioning
confidence: 96%
“…They reported a quiescent period of some 3 years before the 1988 large earthquake. Subsequently, Shanker et al (2010) reported that the earthquakes of M ≥ 7.5, including the two great earthquakes of 1897 and 1950 in the NER were preceded by anomalous low seismicity, some 11 to 27 years before their occurrences. Such precursor anomaly, before 11-27 years, lead us nowhere to predict an earthquake for the benefit of society.…”
Section: Earthquake Precursormentioning
confidence: 99%